2010
DOI: 10.1111/j.1365-2427.2010.02434.x
|View full text |Cite
|
Sign up to set email alerts
|

A major shift in Daphnia genetic structure after the first ice‐free winter in a German reservoir

Abstract: Summary 1. Climate warming may cause disruption of trophic linkages in aquatic ecosystems and lead to changes in abundance and genetic structure of zooplankton populations. We monitored the community of the Daphnia galeata‐hyalina hybrid complex in the Saidenbach Reservoir (Saxony, Germany) using allozyme electrophoresis for three consecutive years (2005–07), including one (2007) following an unusually warm winter that prevented the formation of ice cover for the first time in the history of the reservoir. 2. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 30 publications
(84 reference statements)
4
35
0
Order By: Relevance
“…The contribution of individuals surviving the winter period to the next season's population may substantially differ, both among different localities (as observed by us) and among years within the same locality [19]. The overwintering clones may belong to the most successful ones within the population.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of individuals surviving the winter period to the next season's population may substantially differ, both among different localities (as observed by us) and among years within the same locality [19]. The overwintering clones may belong to the most successful ones within the population.…”
Section: Discussionmentioning
confidence: 99%
“…In cold-winter years, genetic diversity of Daphnia increased significantly during spring, presumably due to a higher contribution of emergence from resting eggs to population growth (Hülsmann et al 2012). In addition, the genetic composition of the population differed substantially between cold-and warm winter years (Zeis et al 2010). This will affect physiological capabilities of the spring population to cope with high temperature and/or low oxygen (Pinkhaus et al 2007;Paul et al 2012), life history strategies, and potentially also the inducibility of defense strategies against predators (Hülsmann and Wagner 2007).…”
Section: Changes In Biodiversitymentioning
confidence: 99%
“…These field observations were confirmed by laboratory experiments, where observed reaction norms mirrored life-history trait values from natural populations (Bernot et al 2006). Zeis et al (2010) showed that temperature regime changes may result in a shift in the balance between D. galeata and D. hyalina in their hybrid complex community (populations contain parental as well as hybrid genotypes). Daphnia galeata and D. hyalina genotypes are characterised by different potentials for resting egg production and different timings of ephippia formation and hatching events.…”
Section: Interspecific Differences and Its Consequences For Shifts Inmentioning
confidence: 55%
“…These authors observed that overwintering D. galeata clones appeared after an unusually warm winter in 2007, whereas all of the other years investigated, which had cold winters, were dominated by D. hyalina genotypes, which hatched from resting eggs. Zeis et al (2010) concluded that the increasing temperatures predicted under the context of climate change may favour overwintering animals, leading to an increase in the contribution of these genotypes to the population. The authors did not consider consequences of such phenomena for the genetic diversity of this community, although it might be expected that overwintering populations will be genetically less diverse than formed by hatchlings (e.g.…”
Section: Interspecific Differences and Its Consequences For Shifts Inmentioning
confidence: 99%